ESTIMATION OF PARAMETERS OF THE ELASTIC TERMINAL OF MARK KP-5.2 - Kostiuk, M. D.; Rybkin, V. V.; Bondarenko, I. O.; Ivanchenko, N. M. (Science and Transport Progress, 2003)
The numerical rating of parameters of serviceability of the elastic plug КП-5.2 is carried out in this work. The geometrical characteristics of the plug cross section and rigidity of plugs і are determined, and also the verifying calculations on streangth and endurance are carried out